Age and size at maturity in Indonesian women: A norm of reaction?. Issue 5 (4th June 2014) - Sohn, Kitae
Abstract : Objectives: We test (McIntyre and Kacerosky's [2011]: Am J Hum Biol 23:305–312) prediction that the relationship between age at menarche and height switches from negative to positive, in a unidirectional and smooth manner, as the society industrializes. According to this prediction, a mid‐level industrial country should exhibit a weak relationship between the two variables. Methods: The 8, 013 observations are extracted from the Indonesian Family Life Survey, a nationally representative survey. Indonesia is an intermediate case that exists between the small‐scale agrarian societies and industrialized societies examined by McIntyre and Kacerosky. While age at menarche is a recalled and self‐reported variable, height is a measured one. The relationship is informally provided in a figure and formally estimated using ordinary least squares (OLS). Results: The informal finding clearly shows no relationship between age at menarche and height. The OLS results also agree that the relationship is very weak. Specifically, despite the large sample size, the relationship is not statistically significant in a linear manner, regardless of whether the outlier group (age at menarche 10) is included or excluded. Various robustness checks are performed to confirm this finding. Conclusions: Our results lend support to McIntyre and Kacerosky's explanation as to why the relationship between age at menarche and height switches from negative to positive as the society industrializes. Furthermore, our results imply that the model (the Day and Rowe model) and theory (life history theory) on which this explanation is based are plausible. Am. J. Hum. Biol. 26:713–715, 2014. © 2014 Wiley Periodicals, Inc.